2013
DOI: 10.1073/pnas.1310905110
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Jagged 1 and 2 levels prevents cerebral arteriovenous malformations in matrix Gla protein deficiency

Abstract: Significance Cerebral arteriovenous malformations (AVMs) are common vascular abnormalities that may lead to strokes. Signaling by bone morphogenetic proteins (BMPs) and Notch play important roles in the formation of cerebral AVMs, but the cross-talk between the pathways is poorly understood. We report that gene deletion of matrix Gla protein (MGP), a BMP inhibitor, causes cerebral AVMs in mice by activating activin receptor-like kinase 1, a BMP receptor. This activation enhances Notch activity and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
90
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 37 publications
7
90
1
Order By: Relevance
“…Biol. 60: 71-76 (2016) ( Yao et al, 2011), the maintenance of BMP and Notch signaling balance and the maintenance of normal endothelial cell function (Sharma and Albig, 2013;Yao et al, 2013).…”
Section: Abstract: Mgp Angiogenesis Heart Development Brain Develmentioning
confidence: 99%
See 3 more Smart Citations
“…Biol. 60: 71-76 (2016) ( Yao et al, 2011), the maintenance of BMP and Notch signaling balance and the maintenance of normal endothelial cell function (Sharma and Albig, 2013;Yao et al, 2013).…”
Section: Abstract: Mgp Angiogenesis Heart Development Brain Develmentioning
confidence: 99%
“…The increase of this BMP type I receptor enhances the expression of Notch ligands Jagged 1 and 2, which increases Notch activity and alters the expression of Ephrin-B2 and Ephrin receptor B4, arterial and venous endothelial markers, respectively. MGP is responsible for maintaining the balance between BMP and Notch signaling and promotes a normal brain vasculature (Yao et al, 2013). Furthermore, earlier in 2013 another study highlighted MGP importance during angiogenesis, namely in promoting angiogenic resolution and vascular stabilization (Sharma and Albig 2013).…”
Section: In Some Regions Of the Atrium (Yellow Hastag) And In The Sinmentioning
confidence: 99%
See 2 more Smart Citations
“…ACVRL1 will inhibit BMP and induce Notch ligands, resulting in deregulation of endothelial differentiation and AVM development in MGP null animal models. 56 Activation of Notch4 (int-3) in the endothelium of animal models during brain development has been associated with AVM formation; it can be activated using a tetracycline-regulatable system. It has been demonstrated that int-3 activation alone is sufficient to induce and sustain the growth of abnormally large vasculature and shunting, which are the hallmarks of AVMs.…”
Section: Avm Formationmentioning
confidence: 99%